Locally Delivered Salicylic Acid from a Poly(anhydride-ester): Impact on Diabetic Bone Regeneration - Wada, Keisuke (2013)
Diabetes mellitus (DM) involves metabolic changes that can impair bone repair, including a prolonged inflammatory response. A salicylic acid-based poly(anhydride-ester) (SA-PAE) provides controlled and sustained release of salicylic acid (SA) that locally resolves inflammation. This study investigates the effect of polymer-controlled SA release on bone regeneration in diabetic rats where enhanced inflammation is expected. Fifty-six Sprague-Dawley rats were randomly assigned to two groups: diabetic group induced by streptozotocin (STZ) injection or normoglycemic controls injected with citrate buffer alone. Three weeks after hyperglycemia development or vehicle injection, 5 mm critical sized defects were created at the rat mandibular angle and treated with SA-PAE/bone graft mixture or bone graft alone. Rats were euthanized 4 and 12 weeks after surgery, then bone fill percentage in the defect region was assessed by micro-computed tomography (CT) and histomorphometry. It was observed that bone fill increased significantly at 4 and 12 weeks in SA-PAE/bone graft-treated diabetic rats compared to diabetic rats receiving bone graft alone. Accelerated bone formation in normoglycemic rats caused by SA-PAE/bone graft treatment was observed at 4 weeks but not at 12 weeks. This study shows that treatment with SA-PAE enhances bone regeneration in diabetic rats and accelerates bone regeneration in normoglycemic animals.